THREE-DIMENSIONAL ANALYSIS OF SUBMACULAR PERFORATING SCLERAL VESSELS BY ENHANCED DEPTH IMAGING OPTICAL COHERENCE TOMOGRAPHY. Issue 6 (June 2018) - Rothenbuehler, Simon P.; Maloca, Peter; Scholl, Hendrik P. N.; Gyger, Cyrill; Schoetzau, Andreas; Kuske, Lorenz; Mosimann, Nathanael; Zweifel, Sandrine A.; Barthelmes, Daniel; Tufail, Adnan; Hasler, Pascal W.
Abstract : Purpose: To analyze submacular perforating scleral vessels (PSVs) using enhanced depth imaging spectral domain optical coherence tomography (EDI-SDOCT). Methods: Twenty-two eyes of 11 healthy women were included in this retrospective study. Central EDI-SDOCT scans (3 × 4.5 × 1.9 mm, 13.5 mm 2 scan area) were acquired and postprocessed by denoising, manual sclera segmentation, and PSV investigated by five graders. Results: Mean age was 22.4 ± 6.2 years. Mean refractive error was −0.44 ± 0.8 diopters. Mean axial length was 23.08 ± 0.63 mm. The coefficient of agreement for grading was good. Mean number of submacular PSVs was 0.33 ± 0.2 per mm 2 (range from 0 to 9 per eye). Subfield analysis showed 0.2 ± 0.5 (range 0–2) and 2.1 ± 1.8 (range 0–7) vessels, respectively, for central 1-mm diameter and 3-mm diameter. Quadrant analysis showed 0.7 ± 0.9, 0.5 ± 0.9, 0.3 ± 0.6, and 0.4 ± 0.6 vessels, respectively for superior, inferior, nasal, and temporal quadrants. Total number of PSV showed no significant side difference (median difference 0.5, confidence interval −3.0 to 3.0, P = 0.94) or an influence of axial length ( P = 0.16). Conclusion: This is the first description of three-dimensional EDI-SDOCT visualization of submacular PSV in healthy eyes. This method allows for in vivo imaging of a critical component of outer retinal perfusion at the posterior pole. Abstract : Supplemental Digital Content is Available in the Text.Perforating scleral vessels can be investigated by EDI-OCT. Image postprocessing with speckle noise reduction and three-dimensional visualization allows for quantification and analysis of vessel structures possibly important for choroidal perfusion of the foveal outer retina. The authors found a mean number of 0.33 ± 0.2 perforating scleral vessels per mm 2 in the submacular area.